2015
DOI: 10.1016/j.jmig.2014.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Operative Time Longer Than 180 Minutes in Abdominal Hysterectomy is Predictive of 30-Day Perioperative Complications

Abstract: to operative time. Operative times were divided into 60-minute intervals and complication rates analyzed. Bivariate analysis and multivariate regression modeling were performed to assess the association between operative time and complications. Results: A total of 16,864 abdominal hysterectomy procedures were identified. Rates of 30-day overall, medical, surgical complications, and reoperation were 12.4%, 9.2%, 4.2%, and 1.7%, respectively. Complication rates increased significantly with increasing operative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Several studies have reported that prolonged operative time was associated with a negative surgical outcome. 16,17 In a retrospective cohort study of 28 366 women form the NSQIP data, operative time more than 180 minutes was a predictor for surgical site infection in both abdominal hysterectomy and LAVH groups. 16 In a study of 16 864 women who underwent abdominal hysterectomy, operative time more than 180 minutes was independently predictive of overall complications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported that prolonged operative time was associated with a negative surgical outcome. 16,17 In a retrospective cohort study of 28 366 women form the NSQIP data, operative time more than 180 minutes was a predictor for surgical site infection in both abdominal hysterectomy and LAVH groups. 16 In a study of 16 864 women who underwent abdominal hysterectomy, operative time more than 180 minutes was independently predictive of overall complications.…”
Section: Resultsmentioning
confidence: 99%
“…16 In a study of 16 864 women who underwent abdominal hysterectomy, operative time more than 180 minutes was independently predictive of overall complications. 17 Operative time is probably directly proportional to complicated surgery and represents several categories of harmful events, such as insufficient prophylactic antibiotics, breaking sterile technique, tissue damage owing to prolonged traction or manipulation, and risk of thermal dysregulation. 16 Thus, these potential risk factors should be monitored, especially in women subjected to longer surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] This is important as prolonged operative times are associated with poorer patient outcomes. 25,26 Gestational age at hospitalization (wk) 33 5/7 AE 2 4/7…”
Section: Discussionmentioning
confidence: 99%